PROCLAMACIÓN DE LUIS I COMO REY DE ESPAÑA EN MURCIA - Torres-Fontes Suárez, Cristina (Imafronte, 1993)
On 12th of March, 1724, the city of Murcia carried out the solemn celebrations organized by the City Mayor and Councillors as acts of proclamation and reverence to the King Luis the First of Spain. It was a feast day which gatheredpeople from city and country; a feast for everybody, but with different and defined places for different social classes. From a high platform, sorrounded by full uniformed military men and dragoons, King Luis' letter was read to the people. After shooting artillery salutes and giving cheers for the King, the civic procession returned to the City Hall.